Reason and the heart : a prolegomenon to a critique of passional reason - Wainwright, William J. (Ithaca : Cornell University Press, 1995)
Between the opposing claims of reason and religious subjectivity may be a middle ground, William J. Wainwright argues. His book is a philosophical reflection on the role of emotion in guiding reason. There is evidence, he contends, that reason functions properly only when informed by a rightly disposed heart.
Jonathan Edwards and the heart -- John Henry Newman and the "Grammar of Assent" -- William James, rationality, and religious belief -- Subjectivism and circularity -- The specter of relativism.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Edwards, Jonathan, -- 1703-1758.; Newman, John Henry, -- 1801-1890.; James, William, -- 1842-1910.; Edwards, Jonathan, -- 1703-1758; James, William, -- 1842-1910; Newman, John Henry, -- 1801-1890; Faith and reason; Faith and reason -- Christianity; Subjectivity -- Religious aspects; Subjectivity -- Religious aspects -- Christianity; Faith and reason; Faith and reason -- Christianity; Subjectivity -- Religious aspects; Subjectivity -- Religious aspects -- Christianity; Glaube; Vernunft; RELIGION / Philosophy; PHILOSOPHY / Religious; Electronic books